How the Service Quality of Regional Airport Affects Tourist Satisfaction with Airport Services and Their Intention to Revisit Secondary Cities: An Exploratory Study - Ekkarat Suwannakul; Siriporn Khetjenkarn; Supaporn Wichaidit (Journal of Quality Assurance in Hospitality & Tourism, 2023)
This study aims to identify dimensions for measuring tourists’ perceptions of the service quality of regional airports in secondary tourist cities and to investigate the causal relationship between regional airport service quality, tourist satisfaction with airport services, and revisit intention to secondary tourist cities in Thailand. A total of 886 responses are analyzed using the structural equation modeling technique. This study explored four dimensions to measure the service quality of regional airports, namely, diversion, convenience, the efficiency of airport function, and access. Empirical results reveal the direct effects of three dimensions of diversion, convenience, and access on tourist satisfaction with airport services. This study also found indirect effects of the three dimensions on destination revisit intention through tourist satisfaction. Furthermore, the article affirms a strong link between tourist satisfaction with airport services and their intention to revisit the secondary tourist cities.
Keywords: Customer Service Quality and Loyalty; Aviation Industry Analysis and Trends; Diverse Aspects of Tourism Research